2023
DOI: 10.3390/nano13162287
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Bioactive Glasses: The Newest Achievements and Breakthroughs in the Area

Abstract: Bioactive glasses (BGs) are especially useful materials in soft and bone tissue engineering and even in dentistry. They can be the solution to many medical problems, and they have a huge role in the healing processes of bone fractures. Interestingly, they can also promote skin regeneration and wound healing. Bioactive glasses are able to attach to the bone tissues and form an apatite layer which further initiates the biomineralization process. The formed intermediate apatite layer makes a connection between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 244 publications
0
1
0
Order By: Relevance
“…It is important to mention that the ionic portion of bioceramics influences various osteogenic and angiogenic genes such as HIF-1α and TNF-α for bone regeneration and PI3K/AKT and MAPK/ERK cascades for vascularization[ 14 ]. Conversely, the porosity of the material is considered a critical characteristic which has to be controlled for inadequate nutrient delivery and determining the mechanical strain required for cellular attachment and proliferation[ 20 ]. One of the obstacles to use clinically the bioceramics is the complexity of matching patient–specific destruction besides the alteration in the degradability behavior of some bioceramics in vitro or in vivo .…”
Section: Bioceramics In Hard Tissue Regenerationmentioning
confidence: 99%
“…It is important to mention that the ionic portion of bioceramics influences various osteogenic and angiogenic genes such as HIF-1α and TNF-α for bone regeneration and PI3K/AKT and MAPK/ERK cascades for vascularization[ 14 ]. Conversely, the porosity of the material is considered a critical characteristic which has to be controlled for inadequate nutrient delivery and determining the mechanical strain required for cellular attachment and proliferation[ 20 ]. One of the obstacles to use clinically the bioceramics is the complexity of matching patient–specific destruction besides the alteration in the degradability behavior of some bioceramics in vitro or in vivo .…”
Section: Bioceramics In Hard Tissue Regenerationmentioning
confidence: 99%
“…Compared to ceramics, which possess an ordered crystalline structure, bioglass is an amorphous glass material lacking a distinct crystal arrangement. The primary constituents of bioglass include silica, calcium oxide, phosphorus oxide, sodium oxide, potassium oxide [ 29 ], etc. Bioglass offers excellent biocompatibility, bioactivity and osseointegration [ 30 ] and efficacy in loading therapeutic molecules and subsequent delivery [ 31 ].…”
Section: Classification Of Current Bone Repair Materialsmentioning
confidence: 99%
“…Research has demonstrated the capacity of bioactive glass not only to deliver critical ions for remineralization but also to initiate the formation of hydroxy carbonate apatite (HCA), which closely resembles the mineral composition of natural teeth. This effect is pivotal for the in vitro remineralization of dental enamel, as detailed in studies exploring the interaction of bioactive glasses with human dental tissues [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine anions can be delivered from NaF, amine fluorides, and bioactive glasses. The integration of bioactive glass in dental care products, especially those containing fluoride, marks a significant advancement in efforts to enhance enamel demineralization resistance [10,11]. The dual function of bioactive glasses in releasing essential ions for remineralization while also providing fluoride ions contributes to the formation of fluorohydroxyapatite, a more resilient variant of the mineral, thus offering an added layer of protection against caries and erosion [12].…”
Section: Introductionmentioning
confidence: 99%